Dynamics Of The Sinoman Hadrah Al Irsyad Tradition, Kintapura Village, Kintap District, Tanah Laut District, 2010-2022 - Muhammad Sabirin; Rusdi Effendi; Daud Yahya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Sinoman Hadrah consists five or six poetry singers well as tambourine players, then jellyfish umbrella players and accompanied Sinoman Hadrah dancers numbering 20 to 30 people based on number of members while holding small triangular flags inscribed with Arabic letters (Asmaul Husna). The research method in this article is a historical method consisting of the processes of historiography, heuristics, criticism and interpretation used in this research. The author has ensured that the sources used in the research are trustworthy. Among them are Mr. Guru Marhani, Abdul Manap, Muhammad Helman, Rian Sidiq, Muhammad Seman Alfarisi, Emansyah, Middad H. Rahmadi, Masliani, and Mr. Guru Marhani. They include Coach Sinoman Hadra Al Irsyad and his members, as well as the Kintapura community. After ensuring existing sources meet the requirements as candidates for the interview. After obtaining the required data, the researcher analyzes and presents the research results using historiography. The results of the research show that the existence the Sinoman Hadrah Al Irsyad Tradition experiences setbacks and developments every year. caused several factors such as not knowing the origins the Sinoman Hadrah Al Irsyad Tradition, the lack of interest of young people in taking part as well as the role of citizens in maintaining its existence. This research aims to find out the origins of the Sinoman Hadrah Al Irsyad Tradition as well as the dynamics of the reduction and development of Sinoman Hadrah Al Irsyad so that the role of the Kintapura community in maintaining its existence will remain with the community.